Proposed Methodology for the Annoyance Penalty of Amplitude Modulated Wind Turbine Noise - Rufin Makarewicz (Archives of Acoustics, 2022)
Amplitude modulation increases the annoyance caused by wind turbine noise. One gets the improved annoyance when a penalty is added to the measured or calculated time-average sound level. The amplitude modulated wind turbine noise consists of pulses. Each of them could be characterized by the short timeaverage sound level and the modulation depth. The latter determines the pulse penalty. This paper shows how to calculate the improved annoyance of amplitude modulated wind turbine noise, when the short time-average sound level and the penalty for each pulse are known. A special case of identical pulses is discussed. The proposed methodology needs to be tested by research.